Effect of crosslinking on morphology and phase inversion of EPDM/PP blends - Antunes, C. F. (2012)
This study investigates the effect of cross-linking on morphology and phase inversion of EPDM/PP blends. Several EPDM/PP blends without and with cross-linking agent were prepared in a Haake batch mixer under constant conditions. The morphology was studied by electronic microscopy (SEM and TEM), and cross-linking was followed by EPDM gel content and swelling. The results showed that the position of the phase inversion region is essentially governed by composition, being independent of the viscosity ratio of the EPDM/PP blend. The TPVs’ morphology of the EPDM/PP blend, with 70 and 50 wt% of PP, consists of EPDM cross-linked particles dispersed in the PP matrix. For EPDM-rich composition (30 wt% of PP), the TPVs’ morphology appears to be co-continuous. Even though dynamic vulcanisation of the rubber phase always improves the dispersion of the EPDM phase, complete phase inversion (from fully dispersed PP in the EPDM matrix to EPDM fully dispersed in the PP matrix) was achieved only with low viscosity EPDM. The results suggest that phase inversion driven by cross-linking can occur at viscosity ratios lower than those estimated for the respective EPDM/PP blends at phase inversion.